Identification and quantitation of isomeric pneumococcal polysaccharides by partial chemical degradation followed by mass spectrometry. (1st August 2022) - Manheim, Jeremy; Lin, Mingxiang; Kong, John; Biba, Mirlinda; Zhuang, Ping
Abstract: Quantitation of isomeric pneumococcal polysaccharides in vaccines is a challenging task due to mixture complexity, their low quantities, and identical monosaccharide compositions. Differentiation and quantitation of isomeric pneumococcal polysaccharides were investigated here based on a partial chemical degradation mass spectrometry approach to generate an oligosaccharide marker for one isomer, and not the other. Mild base conditions were successful at generating unique ions for the isomers with the weakest glycosidic bonds, while strong base and acid conditions were successful at generating unique ions for the more stable isomers. Linear relationships between the ion abundance of the oligosaccharide marker and the starting pneumococcal polysaccharides concentration were established for all isomers. Furthermore, precision measurements for each method were below 12% demonstrating good robustness. Therefore, partial chemical degradation followed by mass spectrometry was successful at differentiating and quantifying isomeric pneumococcal polysaccharides and may be adopted for other bacterial types. Graphical abstract: Unlabelled Image